2020
DOI: 10.1111/plb.13171
|View full text |Cite
|
Sign up to set email alerts
|

Warming weather changes the chemical composition of oat hulls

Abstract: The current threats of climate change are driving attention away from the petrochemical industry towards more sustainable and bio‐based production processes for fuels and speciality chemicals. These processes require suitable low‐cost starting material. One potential material assessed here is the oat hull. Its overall chemical composition has so far not been fully characterized. Furthermore, it is not known how it is affected by extreme weather events. Oat hulls (Kerstin and Galant varieties) grown during ‘nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 26 publications
0
21
1
Order By: Relevance
“…The physicochemical characteristics of OH, a byproduct of the food industry, vary widely with type of seed, weather conditions, and dehulling process. Schmitz et al (2020) reported that the starch and insoluble fiber (cellulose, hemicellulose, and lignin) contents of OH varied from 2.5 to 16.3% and from 62.6 to 83.9%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The physicochemical characteristics of OH, a byproduct of the food industry, vary widely with type of seed, weather conditions, and dehulling process. Schmitz et al (2020) reported that the starch and insoluble fiber (cellulose, hemicellulose, and lignin) contents of OH varied from 2.5 to 16.3% and from 62.6 to 83.9%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…It has become increasingly more attractive in recent years due to the discovery of its many health benefits such as lowering cholesterol and reducing glycemic response [ 37 ]. In 2017, the global output of oats attained 26 million tons, and this is expected to increase further in the future [ 38 ]. Bract color is one of the most important characters in variety identification, and yellow bracts are commonly seen in oat cultivars, such as ‘Triple Crown’ and ‘Qingyin No 1’, while black bracts are found in other cultivars, including ‘Qinghai 444’ and ‘Qingyan No 1’ [ 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…While the alteration of macroscopic factors such as grain yield, plant height and lodging severity influenced by growing conditions of oats is well demonstrated by the above-cited studies, our knowledge of the effects of growing conditions on the chemical composition as well as on nutritive and functional properties of oat grain is rather limited. The chemical composition of the oat hull is greatly influenced by weather variations during the oat growth phase ( Schmitz et al, 2020 ), but no similar data is available on composition changes in the whole grain. Here, we examined the stability of protein composition properties of winter oats in relation to the excess water available during the grain-filling period.…”
Section: Discussionmentioning
confidence: 99%